2014
DOI: 10.15560/11.1.1516
|View full text |Cite
|
Sign up to set email alerts
|

Fish from urban tributaries to the Vermelho River, upper Paraguay River Basin, Mato Grosso, Brazil

Abstract: Abstract:The fish fauna of urban streams is still poorly known, it difficult to assess the effects of urbanization expansion on fish species composition, for this reason the aim of this study was to provide a checklist of species that compose the ichthyofauna of six urban streams, tributaries to the Vermelho River, upper Paraguay River Basin, Rondonópolis, Mato Grosso State, Brazil. The samples were performed with seine nets on a spatial gradient of 75 m, and with sieves for a period of 15 minutes in each site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
1
5
0
8
Order By: Relevance
“…Other studies conducted in streams of the Paraguay River Basin reported similar results (Oliveira et al 2015, Vizzotto & Castro 2015, which reflect typical species patterns for Neotropical icthyofauna (Reis et al 2016).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Other studies conducted in streams of the Paraguay River Basin reported similar results (Oliveira et al 2015, Vizzotto & Castro 2015, which reflect typical species patterns for Neotropical icthyofauna (Reis et al 2016).…”
Section: Discussionsupporting
confidence: 70%
“…However, the total number of species would likely be higher if the plateau streams had been included (Alho & Sabino 2012). Numerous studies have been carried out in the basin over the past two decades, including the floodplain region (Catella & Petrere-Jr 1996, Willink et al 2000, Junk et al 2006, Baginski et al 2007, Pacheco & Silva 2009, PainsSilva et al 2010, Pains-Silva et al 2014, Polaz et al 2014, Botini et al 2015and Severo-Neto et al 2015 and plateau waters (Súarez et al 2007, Terra & Sabino 2007, Casatti et al 2010, Castro & Vizzotto 2013, Krinski et al 2015and Oliveira et al 2015. In studies of the plateau portion of the basin, analyses at small spatial scales were the predominant.…”
Section: Introductionmentioning
confidence: 99%
“…The inventory of fish conducted by Oliveira et al (2015) in urban tributaries of the Vermelho River also confirmed the predominance in number of species of Characiformes (29) and Siluriformes (16), followed by representatives of Gymnotiformes (6), Perciformes (4) and Cyprinodontiformes (1). However, it should be emphasized that the methodologies used for the capture of fish in our study were different to those applied by Castro and Vizzotto (2013) and Oliveira et al (2015).…”
Section: Discussionmentioning
confidence: 58%
“…However, it should be emphasized that the methodologies used for the capture of fish in our study were different to those applied by Castro and Vizzotto (2013) and Oliveira et al (2015). For Silveira et al (2010), the use of a single sampling method is impossible to be applied in all freshwater habitats, since the water courses are very heterogeneous.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation